Like usual, we can solve this question using an equation. Let’s assume that John’s age is x, and his sister’s age is y.
x = 2y
To figure out John’s age, we need to know his sister’s age. He’s 2 times older than his sister.
x + y = 27
The sum of their ages is 27, and we can substitute the value of x here to figure out y.
2y + y = 27
We can now simplify this, and get y by itself.
3y = 27
Now, we can divide by 3 to get the y by itself.
y = 9
We now know that John’s sister is 9.
Now, using our original equation, we can substitute in the value of y.
x = 2(9)
We can simplify this.
x = 18
John’s age is 18!
Hope this helps.